A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Which linear function represents the line given by the pointslope equation y + 1 = –3(x – 5)?
f(x) = –3x – 6
f(x) = –3x – 4
f(x) = –3x + 16
f(x) = –3x + 14
anonymous
 one year ago
Which linear function represents the line given by the pointslope equation y + 1 = –3(x – 5)? f(x) = –3x – 6 f(x) = –3x – 4 f(x) = –3x + 16 f(x) = –3x + 14

This Question is Closed

Mehek14
 one year ago
Best ResponseYou've already chosen the best response.1first use distribution \(3(x5)\\3*x=3x\\3*5=15\\y+1=3x+15\)

Mehek14
 one year ago
Best ResponseYou've already chosen the best response.1what is 15  1 @jonestyrese15

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0i think the answer is d

Mehek14
 one year ago
Best ResponseYou've already chosen the best response.1@Imtiaz7 sort of late :P

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0can u help me with one more

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0The equation of a linear function in pointslope form is y – y1 = m(x – x1). Harold correctly wrote the equation y = 3(x – 7) using a point and the slope. Which point did Harold use? When Harold wrote his equation, the point he used was (7, 3). When Harold wrote his equation, the point he used was (0, 7). When Harold wrote his equation, the point he used was (7, 0). When Harold wrote his equation, the point he used was (3, 7).

Mehek14
 one year ago
Best ResponseYou've already chosen the best response.1you have to find which point is on the line y = 3(x – 7)

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Which equations and/or functions represent the graphed line? Check all that apply. f(x) = 0.2x  4 f(x) = 0.5x + 2 f(x) = x + 2 y – 3 = (x – 2) y – 1 = 0.5(x + 2)

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0Which linear function represents the line given by the pointslope equation y + 1 = –3(x – 5)? f(x) = –3x – 6 f(x) = –3x – 4 f(x) = –3x + 16 f(x) = –3x + 14
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.